(untitled) (Salam International Academic Journal, 2025)
Migration is a globally recognized phenomenon in the contemporary world, and Afghanistan is no exception. Over the past several decades, insecurity, economic hardships, unemployment, social inequalities, and various other factors have compelled a significant number of Afghans to leave their homeland and migrate to foreign countries. This research is significant in that it aims to identify and analyze the social drivers of Afghan migration, explore the relationship between social issues and migration, and assess the role of government and international organizations in providing potential solutions. The primary objective of this study is to identify the social causes behind Afghan migration to foreign countries, evaluate the relationship between these causes and the phenomenon of migration, and outline viable social interventions for migration prevention. Additionally, the research investigates the role of governmental and international institutions in mitigating migration trends. This study employed a quantitative and descriptive-analytical methodology, utilizing a survey-based approach. Data were collected via a structured questionnaire distributed through Google Forms, with responses obtained from 215 participants. The core research question addressed in this study is: What are the social causes of Afghan migration to foreign countries, and what solutions can be proposed to address them? Findings reveal that the key drivers of Afghan migration include economic challenges, unemployment, conflict, social inequalities, lack of employment opportunities, administrative corruption and bribery, social pressures, and limited access to healthcare services. Regarding solutions, most respondents emphasized the need for reforms in the economic, administrative, educational, and healthcare sectors, while others identified job creation as a fundamental remedy. Overall, the research concludes that if a conducive economic, administrative, and social environment is established, 91.16% of people would not feel the need to migrate. These findings underscore the importance of implementing fundamental reforms, anti-corruption measures, job creation initiatives, support for the private sector, expansion of vocational education, and ensuring social justice to effectively reduce migration pressures.